Biological Activity of Some Essential Oils on Fifth Instar Nymphs of Ommatissus lybicus (Homoptera: Tropiduchidae) - saad Al-dhamin, Ahmed (Iraqi Journal of Science, 2023)
Dubas bug, Ommatissus lybicus (Asche and Wilson) is one of the major sucking pests of date palm. Both nymphs causes severe damage to the leaves by sucking the cell sap . If the damage is severe, it could cause the death of the date palms. The effect of different concentrations of some natural plant essential oils was evaluated on fifth instar nymphs of the insect. The results clearly demonstrated that the tested oils from mint (Mentha piperata), Parsley (Petroselinum sativum), Clove (Syzygium aromaticum), and Eucalyptus (Eucalyptus globules) to evaluate their effect on fecundity of fertile female resulted from these exposed instars nymphs and hatching of these egg. The corrected mortality and numbers of eggs laid, hatching, were studied. The corrected mortality and reduction of laid eggs and hatching was the highest in Eucalyptus. Then M. piperata followed by Syzygium aromaticum and P. sativum.